The Handbag : to Have and to Hold - Allen, Carmel (London Carlton, 2012)
According to Carmel Allen, the beauty editor of Vogue magazine, the key to assessing a modern girl is the handbag. With over 150 colour photographs, this book offers a celebration of the handbag. An indispensable accessory as well as a key fashion statement, the handbag is portable boudoir, office, bank and emergency kit for women. With chapters on the history of the handbag, a Who's Who of style-shapers, a look at the contents women carry and an A-Z of international designers and brands, this book is suitable for handbag lovers. From the classics - the Chanel quilted bag, the Hermès Kelly, Gucci's bamboo-handled, snaffle designs, and Louis Vuitton's monogram, to artistic creations from Judith Leiber and Nathalie Hambro and celebrity favorites Marc Jacobs, Tory Burch, and Balenciaga, the A-Z section profiles the most coveted and iconic designs ever.
Keywords: Handbags